(untitled) (Multidisciplinary Journal of Science and Technology, 2025)
This article provides a broad scientific analysis of the philosophical concepts embodied in the patterns of the Uzbek national headdress - the skullcap. Through skullcap patterns, such topics as the worldview of the people, their connection with nature, family values, spiritual protection, the continuity of life, cosmic balance, the opposition of good and evil, the transience of time, and cultural identity are deeply studied. Based on historical sources, archaeological finds, ethnic traditions, the influence of Islamic art, and modern research, the symbolic meanings of patterns, the psychological impact of colors, regional differences, and the philosophical foundations of motifs are examined. The article emphasizes the need to preserve skullcap patterns as a national cultural heritage, use them in modern design, strengthen national identity in the context of globalization, and increase the importance of the Uzbek philosophical heritage in the world cultural context. The research serves to broaden the understanding of the philosophical worldview of the Uzbek people, ensure spiritual connections between generations, and ensure the continuity of national values.